Hun var heltinden i “Lykke-Per”: – Moster til Niels Bohr, og hendes skole revolutionerede den danske skoleverden – men i dag kender ingen hendes navn - Blüdnikow, Bent (Pontoppidaniana, 2023)
Abstract Jakobe, the heroine of Henrik Pontoppidan’s novel Lykke-Per (A Fortunate Man), can have been built on a real life model. Jakobe in the novel shares a lot of traits with Hanna Adler, a Jewish lady living in Copenhagen 1859-1947 who, after an MA in Physics from University of Copenhagen opened a private school in Copenhagen. In this article, Bent Blüdnikow describes the interesting life of Hanna Adler, also the aunt of later Danish Nobel prize winner, physicist Niels Bohr.